Integrierter Wettbewerb Innenstadt und Rathaus in Bad Honnef. - (:unkn) unknown (My University, 1977)
1. Rang Prof. Joachim Schürmann mit Margot Schürmann, Rainer Theurich (Köln), 2. Rang Prof. B. von Chamier, Prof. E. von Rudloff (Düsseldorf), 3. Rang Walter von Lom (Köln).
Keywords: Städtebaulicher Wettbewerb; Innenstadt; Rathaus; Stadtplanung; Planung